The effect of iron plaque on lead translocation in soil-Carex cinerascens kukenth. system. Issue 1 (2nd January 2016) - Liu, Chunying; Gong, Xiaofeng; Chen, Chunli; Yang, Juyun; Xu, Sheng
Abstract: A pot experiment was conducted to investigate the effect of iron plaque on Pb uptake by and translocation in Carex cinerascens Kukenth. grown under open-air conditions. Using Scanning Electron Microscopy and Energy Dispersive X-Ray Spectrometry, iron plaque was present as an amorphous coating on root surfaces with uneven distribution. The amount of iron plaque increased significantly with increasing Fe additions regardless of Pb additions. The presence of iron plaque on the root surface of Carex cinerascens Kukenth. increased the concentrations of Pb adsorbed by iron plaque. The Pb percentage in whole roots increased by 14.52% at 500 mg kg −1 Fe treatment than at 0 mg kg −1 Fe, and the distribution coefficient (DC) of Pb and translocation factor (TF) root increased with Fe additions, but translocation factor (TF) shoot decreased with Fe additions. The results suggested that iron plaque could promote the translocation of Pb from soil to roots to some extent, and it played a role to reduce heavy metals pollution of Poyang Lake wetland.